Oral cancer research in Taiwan and mainland China: Scientometric analysis with emphasis on distinctive characteristics - Cheng Xie; Jianbo Ou; Huan Shi; Wei Liu (Elsevier, 2022)
Scientometric analysis of a disease is often conducted to recognize research hotspots and investigate latest trends. In this brief report, we provide a scientometric overview of oral cancer research in Taiwan and mainland China. There were 1924 and 3853 articles on oral cancer research originating from Taiwan and mainland China, respectively. In Taiwan, the risk factors including areca/betel quid chewing, tobacco smoking, and alcohol use were the distinctive keywords. For basic research, genotype, reactive oxygen, p53, mitochondria and caspase-9 were the distinctive keywords. In mainland China, experiment methods such as genetic transfection, gene silencing, colony formation, tumor xenograft were the distinctive keywords. Epithelial mesenchymal transition, long untranslated RNA, protein function, uvomorulin, and Bcl-2 were the distinctive keywords of basic research. Collectively, we hope that these scientometric characteristics will aid clinicians and researchers for obtaining information on oral cancer and can be of guidance for future studies.